2008
DOI: 10.1017/s0022215108002478
|View full text |Cite
|
Sign up to set email alerts
|

Honey as topical prophylaxis against radiochemotherapy-induced mucositis in head and neck cancer

Abstract: This study shows that prophylactic use of pure natural honey was effective in reducing mucositis resulting from radiochemotherapy in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 14 publications
6
82
2
9
Order By: Relevance
“…Biswall et al 9 were the first to use topical honey to successfully manage mucositis due to radiation. Rashad et al 12 reported that prophylactic natural honey is effective in reducing mucositis resulting from radiochemotherapy in patients with head and neck cancer. Our study demonstrated that RJ50 protects against hematological indices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biswall et al 9 were the first to use topical honey to successfully manage mucositis due to radiation. Rashad et al 12 reported that prophylactic natural honey is effective in reducing mucositis resulting from radiochemotherapy in patients with head and neck cancer. Our study demonstrated that RJ50 protects against hematological indices.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is clinical and based on the use of known stomatotoxic therapy along with the timing and location of oral lesions. 6,[8][9][10][11][12][13][14] For several decades, there have been publications which have pointed to the potential of antioxidants to reduce mucosa damage induced by ionizing radiation. Some naturally occurring antioxidants have the advantage of offering an extended window of protection against low-dose and low-dose rate irradiation, including therapeutic potential when administered after irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were used topically applied honey for treatment of oral mucositis like Biswal et al [15], Motallebnejad et al [10], Rashad et al [16], Khanal et al [17], Abdulrhman et al [18] and Sedighi et al [19]. They showed that topically applied honey produced faster healing in patients with oral mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Rashad's study demonstrated that topical application of honey on the oral mucosa 15 minutes before, 15 minutes after, and 6 hours after radiation would cause a significant reduction in radiation induced mucositis. Although there are few reports on the preventive effects of honey in mucositis, most of them have investigated patients who have received radiation therapy for head and neck cancer (1,(18)(19)(20)(21)(22)(23)(24)(25). This study added new information about other high risk patients who undergo induction chemotherapy for leukemia.…”
Section: Control No (%)mentioning
confidence: 99%